CO2 – Based transcritical Rankine cycle coupled with a ground-cooled condenser. (1st October 2021) - Mahmoud, Montaser; Ramadan, Mohamad; Naher, Sumsun; Pullen, Keith; Olabi, Abdul-Ghani
Highlights: Geothermal condenser has a great potential in enhancing the Rankine power cycle. The ground temperature significantly affects the cycle's net output power. Most effective parameters: turbine inlet temperature and the CO2 pipe diameter. The ground heat exchanger is more affected by gas conditions at high heat inputs. Abstract: This paper presents a new system that incorporates the CO2 -based transcritical Rankine cycle with a geothermal condenser. The innovation studied in the current proposed system is the use of a shallow ground heat exchanger to activate a ground-cooled condenser instead of an air-cooled one in a power cycle. This combination is very beneficial for power generation, especially in summer because the ground is more effective than the ambient air in extracting heat from the working fluid passing through the condenser due to its lower temperature. Thus, for the same amount of heat added to the cycle, more power could be produced due to the increase in pressure difference between the gas heater and condenser. Consequently, the operating cost of the system will be reduced. This parametric study covers a wide range of heat source applications with gas temperature and mass flow rate being varied between 500 and 1500 °C and 100–350 kg/hr respectively. The objective is to generate the maximum possible power while minimizing the sizes of the heat exchangers. The results show that the best parameters to be controlled are the turbine inlet temperature and CO2 pipe diameter. The incorporation of ground-cooled condenser significantly enhanced the cycle's performance in which the net output power could be increased by ~ 30% compared to the conventional Rankine cycle. This enhancement mainly depends on the ground's temperature since it directly changes the condensation temperature and hence affects the working fluid expansion.